2012
DOI: 10.1007/s00204-012-0804-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and DNA-damaging properties of glyphosate and Roundup in human-derived buccal epithelial cells

Abstract: Glyphosate (G) is the largest selling herbicide worldwide; the most common formulations (Roundup, R) contain polyoxyethyleneamine as main surfactant. Recent findings indicate that G exposure may cause DNA damage and cancer in humans. Aim of this investigation was to study the cytotoxic and genotoxic properties of G and R (UltraMax) in a buccal epithelial cell line (TR146), as workers are exposed via inhalation to the herbicide. R induced acute cytotoxic effects at concentrations > 40 mg/l after 20 min, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 41 publications
6
62
1
6
Order By: Relevance
“…In liver disease, elevations of LDH are not as great as the increase in aspartate aminotransferase (AST) and alanine aminotransferase (ALT). With glyphosate, increased activity of extracellular lactate dehydrogenase is indicative for membrane damage and it was observed at doses >80 mg/l [17] which is consistent to our research. In the present study structural damage could be correlated with the signifi cant increase (p<0.05) in aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase activities in the second and third month of exposure.…”
Section: Discussionsupporting
confidence: 92%
“…In liver disease, elevations of LDH are not as great as the increase in aspartate aminotransferase (AST) and alanine aminotransferase (ALT). With glyphosate, increased activity of extracellular lactate dehydrogenase is indicative for membrane damage and it was observed at doses >80 mg/l [17] which is consistent to our research. In the present study structural damage could be correlated with the signifi cant increase (p<0.05) in aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase activities in the second and third month of exposure.…”
Section: Discussionsupporting
confidence: 92%
“…These responses were considered of limited quality by IARC and the publication authors indicated that the high dose effects might have been at a dose level exceeding a threshold and possibly associated with high toxicity. Koller et al (2012), MN results not evaluated by IARC, reported positive in vitro MN results in human-derived buccal epithelial cells for glyphosate in the absence of S9 metabolic activation. An unusual feature of this paper was indication of significant cytotoxicity at very low dose levels (20 lg/mL) and with very short exposure times (20 min).…”
Section: Chromosomal Effects In Vitromentioning
confidence: 99%
“…Koller et al (2012) report a positive in vitro MN result for a GBF (result not included in IARC) in buccal epithelial cells derived from a human-neck metastatic tumor. The authors noted that these cells have not been used for genotoxicity assessments and the Expert Panel considered the results in this non-validated system to be of unknown relevance.…”
Section: Chromosomal Effects In Vitromentioning
confidence: 99%
“…In contrast, cell types with the lowest apparent sensitivity were human choriocarcinoma cells (JEG3) (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009;Romano et al, 2010;Mesnage et al, 2013a), human chorioplacental cells (JAr) (Young et al, 2015), human hepatoma cells (HepG2) (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009Gasnier et al, , 2010, murine osteoblast precursor cells (MC3T3-E1) (Farkas et al, 2018), human embryonic kidney cells (HEK293) (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009;Mesnage et al, 2013a), and human primary neonate umbilical vein endothelial cells (HUVEC) (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009). Cytotoxicity has also been detected by other biochemical markers e.g., mitochondrial functions, release of lactate dehydrogenase, cell proliferation determined by the use of sulforhodamine B, or membrane integrity and lysosomal activities indicated by the uptake of neutral red dye (Koller et al, 2012;Defarge et al, 2016). The interaction of between glyphosate and mitochondrial succinate dehydrogenase has been verified by molecular modeling (Ugarte, 2014).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 96%
“…Although reviews of genotoxicity studies deemed DNA damage by glyphosate and glyphosate-based formulations secondary to cytotoxic effects (Kier and Kirkland, 2013;Kier, 2015), DNA-damaging effects and genotoxicity of glyphosate and particularly of its formulations (Roundup R , Glyfos R , Glyphogan R , Glyphosate-Biocarb R , etc.) on vertebrates (murine and human cells) (Bolognesi et al, 1997;Koller et al, 2012;Young et al, 2015;Townsend et al, 2017), cytotoxic effects of glyphosate-based herbicides on human embryonic and placental cells (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009Gasnier et al, , 2010Mesnage et al, 2013a,b), indication of endocrine disrupting effects by showing activity on estrogen receptors in human hormone-dependent breast cancer cells (Thongprakaisang et al, 2013;Mesnage et al, 2017a), inhibition of the biosynthesis of testosterone and estradiol (Romano et al, 2010) and progesterone (Young et al, 2015) or inhibitory effects on aromatase, a key enzyme in steroid hormone biosynthesis (Cassault-Meyer et al, 2014;Defarge et al, 2016), teratogenic effects on vertebrates by inhibiting the retinoic acid signaling pathway (Lajmanovich et al, 2003;Paganelli et al, 2010;Carrasco, 2013), birth defects in rats , and nephrotoxic and hepatotoxic effects of Roundup R have been demonstrated in rats in connection to RR GM maize (originally published in the journal Food and Chemical Toxicology in September 2012, but retracted by the journal in November 2013 following an alleged intervention from the industry stakeholder (Foucart, 2016), and subsequently republished in another journal a year later) . The analysis of kidney and liver tissues from the same rats by molecular profiling (transcriptomics, proteomics, metabolomics) confirmed pathology of these organs in the lowest dose Roundup R treatment group culminating in non-alcoholic fatty liver disease (Mesnage et al, 2015a(Mesnage et al, ,b, 2017a.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%